2013
DOI: 10.2134/agronj2012.0461
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Hybrid Rice Performance in Arkansas

Abstract: Despite the rapid producer adoption of hybrid rice (Oryza sativa L.) in recent years, the economic advantage of hybrid rice in the mid‐southern United States remains disputed. This study compared the economic risk and return of three popularly sown hybrid rice cultivars: XL723, Clearfield (CL) XL729, and CL XL745; and eight conventional rice cultivars: Cheniere, CL 142‐AR, CL 151, Francis, Roy J, Taggart, Templeton, and Wells, using University of Arkansas experimental test plot data from 2006 to 2010. Paddy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
12
0
2
Order By: Relevance
“…The optimal scenario for a cultivar with the lowest GWP Y is for it to have the highest yield and the lowest GWP and for these characteristics to persist across environments and years. Three Southern hybrid cultivars, including CLXL745 tested in the present study, have been shown to yield 1 to 1.7 Mg ha -1 more than the highestyielding conventional alternative (Francis) in Arkansas (Lyman and Nalley, 2013), which is corroborated by our results at AR-1 and AR-2 (Table 4). Thus, given that the lowest CH 4 -emitting cultivar at AR-2 was the hybrid, CLXL745, and that hybrids tend to yield more than conventional Southern cultivars, lower GWP Y values are expected (Table 5).…”
Section: Cultivar Differences In Ch 4 Emissions Global Warming Potensupporting
confidence: 88%
“…The optimal scenario for a cultivar with the lowest GWP Y is for it to have the highest yield and the lowest GWP and for these characteristics to persist across environments and years. Three Southern hybrid cultivars, including CLXL745 tested in the present study, have been shown to yield 1 to 1.7 Mg ha -1 more than the highestyielding conventional alternative (Francis) in Arkansas (Lyman and Nalley, 2013), which is corroborated by our results at AR-1 and AR-2 (Table 4). Thus, given that the lowest CH 4 -emitting cultivar at AR-2 was the hybrid, CLXL745, and that hybrids tend to yield more than conventional Southern cultivars, lower GWP Y values are expected (Table 5).…”
Section: Cultivar Differences In Ch 4 Emissions Global Warming Potensupporting
confidence: 88%
“…In other words, would producers sacrifice profit at the expense of conserving water and/or reducing GWP? Previous research on hybrids in Arkansas has indicated that producers would not sacrifice profit at the expense of conserving water and/or reducing the GWP (Lyman and Nalley, 2013). Lyman and Nalley (2013) reported that hybrids had greater rough‐rice yields, at least as large milling yields, and greater net return relative to non‐Clearfield and Clearfield conventional alternative cultivars in Arkansas and concluded that none of the hybrid cultivars were associated with greater yield risk or yield variance than their conventional counterpart cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research on hybrids in Arkansas has indicated that producers would not sacrifice profit at the expense of conserving water and/or reducing the GWP (Lyman and Nalley, 2013). Lyman and Nalley (2013) reported that hybrids had greater rough‐rice yields, at least as large milling yields, and greater net return relative to non‐Clearfield and Clearfield conventional alternative cultivars in Arkansas and concluded that none of the hybrid cultivars were associated with greater yield risk or yield variance than their conventional counterpart cultivars. This point is important given that producers often value yield stability as much as yield potential, which would indicate that, unlike other water‐ and GHG‐saving production techniques (i.e., alternative non‐flooding irrigation methods), there is no economic disadvantage to adopting hybrid cultivars; in fact, there is probably an economic incentive.…”
Section: Resultsmentioning
confidence: 99%
“…In effect, hybrid acreage in the Mid-South, as a percentage of total harvested acreage, increased from 15% in 2005 to over 40% in 2013 . Previous research in the Mid-South (Arkansas) found that hybrid varieties exhibited mean paddy yield premiums of 1.6 to 2.4 Mg ha -1 relative to the best-performing conventional cultivar ('Francis') and were found to be associated with no increase in yield variability (Lyman and Nalley, 2013). A broad study by Nalley et al (2016) that covered Arkansas and Mississippi observed that hybrid and Clearfield (CL) hybrid varieties had a paddy yield premium over conventional varieties of 1.66 and 1.82 Mg ha -1 , respectively.…”
mentioning
confidence: 96%